2015
DOI: 10.1111/phen.12106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body size on fecundity and sperm management in the parasitoid wasp Anisopteromalus calandrae

Abstract: A large body size is considered to be advantageous to the reproductive success of females as a result of several factors, such as the allocation of more resources to reproduction and the efficient management of sperm transferred by males. In the present study, the effects of female body size, female mating status and additional food availability on fecundity and the offspring sex ratio are investigated in the parasitoid wasp Anisopteromalus calandrae Howard (Hymenoptera: Pteromalidae). Because of haplodiploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…In the experiments below, the amount of sperm transferred to the females was estimated based on the proportion of daughters (fertilized eggs) produced by the females. The rationale for this approach is that studies of A. calandrae that have directly counted the number of sperm in female spermathecae have revealed that females efficiently use the stored sperm when they fertilize eggs in oviposition (Khanh et al 2005;Bressac et al 2009;Kasamatsu and Abe 2015). In our previous study, we confirmed that after laying clutches with mixed sexes (demonstrating that they have been inseminated), females produce only sons (unfertilized eggs), suggesting that they have run out of sperm.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…In the experiments below, the amount of sperm transferred to the females was estimated based on the proportion of daughters (fertilized eggs) produced by the females. The rationale for this approach is that studies of A. calandrae that have directly counted the number of sperm in female spermathecae have revealed that females efficiently use the stored sperm when they fertilize eggs in oviposition (Khanh et al 2005;Bressac et al 2009;Kasamatsu and Abe 2015). In our previous study, we confirmed that after laying clutches with mixed sexes (demonstrating that they have been inseminated), females produce only sons (unfertilized eggs), suggesting that they have run out of sperm.…”
Section: Introductionsupporting
confidence: 61%
“…In our previous study, we confirmed that after laying clutches with mixed sexes (demonstrating that they have been inseminated), females produce only sons (unfertilized eggs), suggesting that they have run out of sperm. This finding was confirmed by dissecting such females, which had no or very few sperm in their spermathecae (Kasamatsu and Abe 2015;unpublished data).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations